Pharmacokinetics of Ketoprofen in Nile Tilapia (Oreochromis niloticus) and Rainbow Trout (Oncorhynchus mykiss) - Greene, Whitney; Mylniczenko, Natalie D.; Storms, Timothy; Burns, Charlene M.; Lewbart, Gregory A.; Byrd, Lynne; Papich, Mark G. (Frontiers in Veterinary Science, 2020)
The objective of this study was to document the pharmacokinetics of ketoprofen following 3 mg/kg intramuscular (IM) and intravenous (IV) injections in trout (Onchorhynchus mykiss) and 8 mg/kg intramuscular (IM) injection in Nile tilapia (Oreochromis niloticus). Plasma was collected laterally from the tail vein for drug analysis at various time intervals up to 72 hours following the injection of ketoprofen. In trout, AUC levels were 115.24 µg hr/mL for IM and 135.69 µg hr/mL for IV groups with a half-life of 4.40 hours and 3.91 hours respectively. In both trout and tilapia, there were detectable ketoprofen concentrations in most fish for 24 hours post-injection. In tilapia, there was a large difference between the R- and S-enantiomers, suggesting either chiral inversion from R- to S-enantiomer or more rapid clearance of the R-enantiomer. AUC values of the S- and R-enantiomers were 510 and 194 µg hr/mL respectively, corresponding to a faster clearance for the R-enantiomer. This study shows that there were very high plasma concentrations of ketoprofen in trout and tilapia with no adverse effects observed. Future studies on the efficacy, frequency of dosing, analgesia, adverse effects, and route of administration are warranted.